(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In Greek mythology, gods and heroes do not directly communicate with ordinary humans, and even romantic relationships are observed. They too belong to the category of beings that help their lovers and partners. Undoubtedly, this situation helped the ancient Greeks to understand themselves better through the gods, to better understand their personal desires and tendencies, their behavior, and also to evaluate their strength in a more appropriate way.